Violence Against Displaced Syrian Women in Lebanon. Issue 18 (September 2019) - Usta, Jinan; Masterson, Amelia Reese; Farver, JoAnn M.
This study used focus group discussions to explore 29 Syrian women's experiences of being displaced refugees in Lebanon. Women reported intimate partner violence (IPV), harassment, and community violence. They experienced difficult living conditions characterized by crowding and lack of privacy, adult unemployment, and overall feelings of helplessness. Most frequently, they used negative coping strategies, including justification and acceptance of IPV and often physically harmed their own children due to heightened stress. Some sought support from other Syrian refugee women. Although the study did not address the root causes of IPV, the results shed light on women's experiences and indicate that training them in positive coping strategies and establishing support groups would help them face IPV that occurs in refugee settings.